Preferential Retention of the LMP-1 Promoter at EBV Integration Sites in Lymphomas: Evidence from Cartilage Hair Hypoplasia and Controls - Zachery W. Dickson; Lari Pyöriä; Annika Kangas; Eetu Pello; Leo Hannolainen; Aino Mutka; Hanna-Leena Kukkola; Pasi Huttunen; Yossra H. S. Zidi-Mouaffak; Klaus Hedman; Mervi Taskinen; Panu E. Kovanen; et al. (Journal of Clinical Immunology, 2026)
Abstract Purpose Cartilage-Hair Hypoplasia (CHH), a rare ribosomopathy characterized by immune deficiency, carries a markedly increased risk of early-onset malignancy, particularly lymphoma. However, the molecular drivers of malignant transformation in CHH, and the contribution of viruses to this process, remain poorly defined. Methods We performed targeted virome sequencing of 41 DNA viruses on FFPE tumor samples (primarily lymphomas) from 15 CHH patients and three malignancy-matched controls per patient. Subsequent analyses comprised Epstein-Barr Virus (EBV) quantification via qPCR, intra-host minor variant (MV) profiling, and high-resolution mapping of viral integration sites using ViroJoin. Results EBV was the only pathogen consistently detected across all CHH tumors, with viral loads exceeding those of controls by more than 400-fold. Aggregate analysis of all full-length EBV genomes revealed minimal intra-host diversity and sparse structural variations, of which inversions were the most common. Strikingly, we detected a non-random pattern of EBV integration into the host genome, with junctions frequently clustering near viral promoters, particularly within LMP1 . Integrations localized preferentially to host genes, occurring 1.3-fold more frequently within genes and 8.2-fold closer to them than expected by chance. Conclusion Our findings identify a distinct genomic signature associated with EBV-positive lymphomas, characterized by non-random EBV integrations into the host genome. We propose that these ectopic viral sequences may act as cis-regulatory elements, potentially dysregulating host gene expression and contributing to malignant transformation and disease severity. These results underscore the importance of virome surveillance for early risk stratification in high-risk populations.